Seed Pattern Characteristics of Different Metering Systems for Soaked Okra Seed - Sahoo, P K; Srivastava, A P (Journal of Agricultural Engineering, 2008)
Soaked okra seed is recommended for planting on ridges for better germination. On soaking for 12 h the okra seed becomes so soft that it is prone to increased seed damage. Four different metering systems were evaluated on the basis of their performance parameters i.e. average spacing, quality of feed index, multiple index, miss index, degree of variation and seed damage for metering soaked okra seed at three levels of cell size and four levels of cell speed. The average spacing observed was close to theoretical spacing for cell size equal to maximum seed dimension in case of inclined plate whereas for other three metering systems the cell size 10% more than the maximum seed dimension gave desired result. The quality of feed index was influenced highly by metering systems, cell size and cell speed. The metering systems influenced the seed damage the most followed by cell size. Considering all the performance parameters, it was concluded that inclined plate metering system was best suited for metering soaked okra seed.